Platelet protein S limits venous but not arterial thrombosis propensity by controlling coagulation in the thrombus - Calzavarini, Sara (Blood, 2020)
Anticoagulant protein S (PS) in platelets (PS(plt)) resembles plasma PS and is released on platelet activation, but its role in thrombosis has not been elucidated. Here we report that inactivation of PS(plt) expression using the Platelet factor 4 (Pf4)-Cre transgene (Pros1(lox/lox)Pf4-Cre(+)) in mice promotes thrombus propensity in the vena cava, where shear rates are low, but not in the carotid artery, where shear rates are high. At a low shear rate, PS(plt) functions as a cofactor for both activated protein C and tissue factor pathway inhibitor, thereby limiting factor X activation and thrombin generation within the growing thrombus and ensuring that highly activated platelets and fibrin remain localized at the injury site. In the presence of high thrombin concentrations, clots from Pros1(lox/lox)Pf4-Cre(−) mice contract, but not clots from Pros1(lox/lox)Pf4-Cre(+) mice, because of highly dense fibrin networks. Thus, PS(plt) controls platelet activation as well as coagulation in thrombi in large veins, but not in large arteries.